Rhodiola rosea as a Medicinal Adaptogen: A Review of Its Antidepressant, Anti-Stress, and Performance-Enhancing Effects - Kutnik, Karolina; Sikora, Gabriela; Woźniak, Martyna; Koguc, Karolina; Kusibab, Karolina; Czechowski, Michał; Skórska, Gabriela; Słomianny, Marcela; Kolada, Karolina; Sajda, Małgorzata (Quality in Sport, 2025)
Background: Rhodiola rosea L. is a traditional medicinal plant recognized for its adaptogenic properties, particularly in enhancing the body’s resistance to physical, chemical, and biological stress. Its pharmacological activity has been attributed mainly to phenylpropanoids such as rosavin and salidroside, which influence stress adaptation mechanisms and central neurotransmission. Aim: The review of the pharmacological action, bioactive compounds, and therapeutic applications of Rhodiola rosea, with a particular focus on its potential role in supporting physical and mental performance under stress-related conditions. Methodology: A review was conducted using PubMed and Google Scholar. Studies investigating the chemical composition, mechanisms of action, and effects of Rhodiola rosea on stress, fatigue, cognitive function, and homeostasis were analyzed and synthesized. Results: Rhodiola rosea has demonstrated benefits in reducing fatigue, improving cognitive function, enhancing physical performance, and stabilizing mood. It also possesses a favorable safety profile, with minimal adverse effects. Conclusions: Rhodiola rosea represents a well-tolerated and biologically active adaptogen with promising applications in managing stress-related fatigue and enhancing resilience to physical and psychological challenges. Further controlled clinical trials are warranted to define its efficacy, optima dosage, and mechanisms of action more precisely.